Case Report: Posterolateral Epidural Supra-C2-Root Approach (PESCA) for Biopsy of a Retro-Odontoid Lesions in Same Sitting After Occipitocervical Fixation and Decompression in a Case of Crowned Dens Syndrome With Brainstem Compression and Displacement - Haas, Patrick; Hauser, Till-Karsten; Kandilaris, Kosmas; Skardelly, Marco; Tatagiba, Marcos; Adib, Sasan Darius (Frontiers in Surgery, 2022)
Background: ´Crowned dens syndrome´ (CDS) is a special form of calcium pyrophosphate dihydrate deposition disease which is characterized radiologically by a halo-like or crown-like distribution in the periodontoid region and clinically by cervical pain. Herein, we will describe our experience of posterolateral epidural supra-C2-root approach (PESCA) for biopsy of retro-odontoid lesions in one surgical session after occipitocervical fixation and decompression in a patient with CDS and massive brainstem compression. Case presentation: A 70-year-old woman presented to our department with a 4-week history of progressive walking impairment, neck pain, neck rigidity, fever, dizziness, slight palsy of the left hand, and multiple fall episodes. Magnetic resonance imaging (MRI) of the craniovertebral junction (CVJ) and cervical spine revealed a lesion of the odontoid process and the retro-odontoid region with mainly solid components, as well as small cystic components, and brainstem compression and displacement. In first step, fusion surgery of the CVJ C0–C4 was performed with occiptocervical decompression. After fusion and decompression the lower lateral part of the C1 arc and the lateral superior part of the left side of the C2 arc were removed. The entry point was located directly above the superior part of the C2 root. A biopsy of the lateral portions of the lesions was obtained by bioptic forceps under microscope guidance. Pathologic examination of the mass revealed deposition of birefringent crystals compatible with calcium pyrophosphate. In addition to the clinical symptoms (especially neck pain), the diagnosis of CDS was made. Nonsteroidal inflammatory drugs (NSAIDs) and colchicine (and later magnesium) were started. At follow-up examination 6 months after surgery, an MRI scan of the cervical spine revealed regression of the pannus and the cyst with replacement of the brainstem, clinical improvement of walking, and increased strength of the left hand. Conclusions: This study demonstrates that PESCA can be used to obtain tissue for pathological analysis in one surgical sitting after fusion and decompression and that fusion, decompression, and PESCA (in the same session) together with subsequent conservative management could be a good alternative for the treatment of CDS.